El impacto de la jurisprudencia del Tribunal de Justicia de la Unión Europea en la definición del principio de libre circulación de mercancías en la Comunidad Andina y el Mercosur - Reyes Tagle, Yovana (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
The Andean Court of Justice (ACJ) and the Permanent Tribunal of Review (PTR) of Mercosur have used the European Court of Justice (ECJ) case law to define the principle of free movement of goods enshrined in the Cartagena Agreement and the Treaty of Asuncion. This paper seeks to analyze the manner in which the ACJ and the PTR have applied the ECJ case law in order to determine the existence of trade restrictions. It is argued that there is a need to developed a contextual interpretation of the principle of free movement of goods in the Andean Community and Mercosur that clarifies and develop the concepts of the Cartagena Agreement and the Treaty of Asuncion in the light of their own integration processes, of which the ACJ and the PTR are part.

El Tribunal de Justicia de la Comunidad Andina (TJCAN) y el Tribunal Permanente de Revisión (TPR) del Mercosur han utilizado la jurisprudencia del Tribunal de Justicia de la Unión Europea (TJUE) para definir el principio de libre circulación de mercancías consagrado en el Acuerdo de Cartagena y el Tratado de Asunción. Este artículo busca analizar de qué manera el TJCAN y el TPR han aplicado dicha jurisprudencia para determinar la existencia de restricciones al comercio. Se plantea que existe la necesidad de desarrollar una interpretación contextualizada del principio de libre circulación de mercancías en la Comunidad Andina y el Mercosur que aclare y desarrolle los conceptos incluidos en el Acuerdo de Cartagena y el Tratado de Asunción a la luz de los propios procesos de integración de los que el TJCAN y el TPR forman parte.
The impact of the European Union Court of Justice case law in the definition of the principle of free movement of goods in the Andean Community and Mercosur
Keywords: Libre comercio; Restricciones a las importaciones; Libre circulación de mercancías; Comunidad Andina; Mercosur; https://purl.org/pe-repo/ocde/ford#5.09.01